TAXONOMIC INVENTORY AND ECOLOGY OF THE RODENTS AND INSECTIVORES OF SILENT VALLEY NATIONAL PARK, KERALA. - DEVIPRIYA, K. S. (2014-17-102) (Vellanikkara DEPARTMENT OF WILDLIFE SCIENCES, COLLEGE OF FORESTRY, 2016)
Abstract Rodents and insectivores accounts for about 55% of the total mammalian diversity of the world and is true with Kerala too. Very little studies have been done on the rodents and insectivores of Kerala and no previous studies have been done in Silent Valley NP. Thus, a study was conducted on the taxonomic inventory and ecology of the rodents and insectivores of Silent Valley National Park, which is one of the few remaining pristine rain forests of Kerala. The objectives was to study the species diversity, relative abundance and habitat preference of the rodents and insectivores - such as squirrels, mice, rats and shrews in Silent Valley National Park. The study was carried out from September 2015 to April 2016. The method used for the study was using Sherman Traps technique. 50 Sherman traps were used in each of the four study locations. The study was carried out in two season viz. monsoon and summer and in two habitat types, evergreen forests and grasslands. Six species of rodents and one species of insectivore were recorded from Silent Valley National Park. The rodents recorded were members of Muridae, Sciuridae and Hystricidae families. These includes Rattus wroughtoni, Golunda ellioti, Ratufa indica, Funambulus tristriatus, Funambulus sublineatus and Hystrix indica. The insectivore observed at SVNP was Suncus murinus of the family Soricidae. Though the rodent and insectivore abundance was more during the monsoon season, there was no significant difference. Similarly though the rodent abundance was more at the evergreen forests, this was also insignificant. Among the microhabitat parameters studied, the climber density has found to be significantly influencing the rodents at Silent Valley. Rattus wroughtoni was the most abundant species of rodent at Silent Valley. Among the rodents of Silent Valley, Ratufa indica is endemic to peninsular India while Funambulus tristriatus, Funambulus sublineatus are endemic to Western Ghats. The Funambulus sublineatus is a threatened species of squirrel seen at Silent Valley and the IUCN Redlist category of this is Vulnerable.